TIME DOSING OF ANTIHYPERTENSIVE TREATMENT AND PROGNOSIS. (June 2022) - de la Sierra, Alejandro; Ruilope, Luis; Martinez-Camblor, Pablo; Vinyoles, Ernest; Gorostidi, Manuel; Segura, Julian; Williams, Bryan
Abstract : Objective: Night BP is the most powerful estimate of cardiovascular prognosis. It has been suggested that bedtime administration of antihypertensive therapy may favour night BP reduction and prognosis. We aimed to evaluate the risk of total and cardiovascular mortality in a large cohort of treated hypertensives, depending on the schedule of treatment administration (entirely in the morning, entirely at bedtime, or combined morning and evening) at the time ABPM was performed. Design and method: Vital status and death due to cardiovascular causes were obtained from death certificates in 26751 treated hypertensives (mean age 62, 60% males), enrolled in the Spanish ABPM Registry between 2004 and 2014, and having a valid 24-h ABPM at entry. Cox-models adjusted for clinical confounders and 24-hour systolic BP were used for HR calculation in groups depending on treatment administration. Results: Among the 26751 evaluable patients, most (76.7%) received their medication exclusively in the morning; 13% exclusively in the evening, and 10.3% in a multiple schedule both in the morning and in the evening. Mortality incidence in these 3 groups were 13.7, 17.8 and 21.8 per 1000 patients/year, respectively. Compared to patients receiving their antihypertensive medication entirely in the morning (reference group), those receiving their medication entirely in the evening did not show a significant increase in the HR for total mortality (1.06; 95%CI: 0.93–1.21) or in cardiovascular mortality (1.15; 0.93–1.41) after adjustment for clinical confounders and 24-hour systolic BP. Patients receiving their antihypertensive medication both in the morning and at bedtime had an increased risk for mortality (1.29; 1.14–1.48) and for cardiovascular mortality (1.46; 1.18–1.80). Additional analyses using double-robust propensity score yielded similar results. Conclusions: Morning or bedtime dosing of the antihypertensive medication has no effect on prognosis. We have found that patients receiving their medication in a multiple schedule, including morning and evening dosing have an increased risk of mortality and cardiovascular mortality, even after adjustment for confounders. However, we cannot exclude other aspects, such as a poorer treatment adherence, being the responsible of this worse prognosis.